SNTAM: secure neuro-fuzzy-based trusted neighbour selection and attackers detection in multipath ad-hoc network. Issue 2 (5th June 2023) - Patil, Sandeep; Admuthe, Lalita; Patil, Meenakshi
An ad-hoc network comprises a set of wireless nodes with no pre-defined infrastructure. The most well-known attribute of a wireless network is dynamic. They also have inadequate channel strength, security belief issues and functioning with narrowed battery power. This study explores the capabilities of working with different attacks like a vampire attack. This attack is forever hindrance to the networks by reducing the node's bandwidth and energy. In addition, the protocol detects a replica attack that can capture the neighbour's address and act as a genuine. These two attacks can spoil the entire system activities and use network abilities. The proposed Secure Neuro-fuzzy Based Trusted Neighbour Selection and Attackers Detection in Multipath Ad-Hoc Network (SNTAM) protocol focused to eliminate these attackers from the network to form the communication path by an optimised way of neuro-fuzzy techniques. The results show that SNTAM gives effective results in securing the network in all the parameters and attributes especially packet delivery ratio (PDR) which is almost 100% and residual energy of nodes which is more than compared protocol. Furthermore, SNTAM protocol can avoid sampled malicious nodes effectively.